Peningkatan Produktivitas Peternak Bebek Melalui Penyediaan Mesin Inkubator Penetas Telur Dengan Sistem Monitoring Di Desa Nglebak Kecamatan Bareng Kabupaten Jombang - Wahyu Arrofiq; Acep Samsudin (Universitas Katolik Widya Karya Malang, 2023)
The community service program carried out by UPN Veteran East Java, especially the KKNT 06 group, aims to improve the knowledge and skills of the duck breeding community in Nglebak Jombang Village, especially in the aspect of hatching. Group 06 focuses on MSMEs of duck breeders because one of our flagship programs is to make an egg incubator machine. After the use of this egg incubator machine, the hope is that business people know that there is a more efficient way to improve the welfare of their business, and another thing that is desired is that the people of Nglebak Village are not left behind about technology in the current era of globalization. We, the KKNT 06 group, will not just let go of the Nglebak Village community, of course we will accompany them from how to make to how to use this tool until the results are clearly visible for the welfare of the Nglebak Village community.